More alike than different: The Spanish and Irish labour markets before and after the crisis - Pablo Agnese; Pablo F. Salvador (Institute for the Study of Labor (IZA), 2011)
This paper analyses the labour markets of Spain and Ireland, which have experienced a severe downturn in the recent global crisis as reflected by the largest increases in their unemployment rates among other developed economies. Spain and Ireland might seem at first to feature very different labour markets, which go from very tight to very flexible labour conditions. Our analysis, however, goes beyond this simplistic argument and brings to light the strong commonalities that seem to have been hidden underground. We estimate a dynamic multi-equation structural model for each country, and then offer two sets of dynamic simulations which account for the swings of the unemployment rates before and after the 2007 crisis. Our results suggest looking beyond the degree of flexibility of both labour markets, just to focus instead on other variables usually neglected by more conventional approaches. In particular, such variables as the growth of capital stock, the growth of labour productivity, and demographics, succeed in explaining a great part of the changes in unemployment in both countries.
urn:nbn:de:101:1-201106013927
Keywords: E24; J21; E22; C32; 330; unemployment dynamics; structural multi-equation models; chain reaction theory; simulations; PIGS